Designing a Catalogue for Metrics - Olsina Santos, Luis Antonio (2002)
In this paper, we introduce a catalogue model as one of the building blocks for a repository of metrics. Particularly, starting from a conceptual model for metrics, we thoroughly discuss a catalogue template for product metrics instantiating it with some Web metrics. A catalogue of metrics basically allows tools, evaluators and other stakeholders to have a service and a consultation mechanism, which starts from a sound specification of the entity type, the attribute definition and motivation, the metric formula, criteria, and application procedures, among other template items. The metrics repository and the cataloguing tool can be appropriately used to support different quality assurance processes such as non-functional requirements specification, quality testing definition, etc. in different phases of the software life cycle. Effective and full-fledged quality assurance processes require not only strategic but also technological support as well.